Kontribusi Jaringan Sekolah Islam Terpadu (JSIT) dalam Pengembangan Pendidikan Islam di Indonesia - Abidin, Zainal; Tobibatussaadah, Tobibatussaadah; Walfajri, Walfajri; Nawa, Agus Trioni (Tapis: Jurnal Penelitian Ilmiah, 2022)
Jaringan Sekolah Islam Terpadu (JSIT) is a new phenomenon in the discourse of Islamic education in Indonesia, which developed rapidly in the Reformation era after the fall of the New Order government in 1998. This article is partly derived from the results of research on the development of JSIT in Indonesia, especially in Lampung and Banten. The results of the study show that the emergence of JSIT was initially pioneered by the Tarbiyah Movement (Gerakan Tarbiyah) which became the embryo of the emergence of the Integrated Islamic School. This movement was originally a da'wah movement that emphasized the individual piety of its members and then moved politically after the fall of the New Order regime in 1998 by establishing the political party PKS (Partai Keadilan Sejahtera), while at the same time engaged in education by establishing JSIT which developed an integrated Islamic education system, and growing rapidly. The emergence of these integrated Islamic schools also gave rise to pro and contra responses, because of their connection with the ideology of the Muslim Brotherhood (Ikhwanul Muslimin), which is considered a representation of radical Islamic groups. However, the learning model developed by JSIT became a new thing which was later adopted by educational institutions outside of JSIT which also established integrated Islamic schools. JSIT has progressed and developed quite massively in Indonesia, although these schools are expensive, but it has not stopped the community from sending their children to school, and most of them come from well-established and educated socio-economic class families. This research also shows that the existence of JSIT has significantly contributed to the development of Human Resources (HR) who are superior in science and religion, because the curriculum is designed to combine general knowledge and religious knowledge at the same time. JSIT in its work has contributed to creating a new educated Muslim group in Indonesia in this contemporary era.